Immunogenicity of the candidate malaria vaccines FP9 and modified vaccinia virus Ankara encoding the pre-erythrocytic antigen ME-TRAP in 1-6 year old children in a malaria endemic area. - Bejon, P; Mwacharo, J; Kai, O; Todryk, S; Keating, S; Lang, T; Gilbert, S; Peshu, N; Marsh, K; Hill, A (2006)
In a phase 1 trial, 22 children in a malaria endemic area were immunised with candidate malaria vaccination regimes. The regimes used two recombinant viral vectors, attenuated fowlpox strain FP9 and modified vaccinia virus Ankara (MVA). Both encoded the pre-erythrocytic malaria antigen construct ME-TRAP. Strong T cell responses were detected by both ex vivo and cultured ELISpot assays. Data from phase 1 trials in adults on anti-vector responses raised by FP9 is presented. These responses partially cross-reacted with MVA, and detectably reduced the immunogenicity of vaccination with MVA. This prompted the comparison of half dose and full dose FP9 priming vaccinations in children. Regimes using half dose FP9 priming tended to be more immunogenic than full dose. The potential for enhanced immunogenicity with half doses of priming vectors warrants further investigation, and larger studies to determine protection against malaria in children are required.